PENGETAHUAN GURU TENTANG GIZI DAN KECACINGAN DI EMPAT SEKOLAH DASAR PENERIMA PMT-AS DI DESA IDT BENGKULU - Trintrin T. Mudjianto (Persagi, 1998)
The study on knowledge of nutrition and worm infestation among elementary school teachers was conducted in four IDT schools in Bengkulu Utara District. Total of 23 teachers was involved as respondents, the data collections was held 6 month after PMT-AS being implementated. Data in knowledge of food utilization and nutrient content and worm infestation prevention of the teachers were collected. The most important result of the study shows that almost all of the respondents have low knowledge on food utilization aand nutrition content and worm infestation prevention as well.Keywords: Nutrition knowledge, worm infestation, scholl feeding program (PMT-AS).